Impact of Monetary Policy on Consumption and Investment in Indonesia - Tiara Nirmala; Catur Sugiyanto; Muhammad Edhie Purnawan (Universitas Negeri Malang, 2022)
Monetary policy transmission mechanism has a complex process since its implementation it involves changes on banking sector, economic actors, the length of time in implementing policies, as well as changes in monetary policy transmission channels according to economic condition of the country. This study aims to examine how consumption and investment respond to monetary shocks that occur in Indonesia. These results indicate that the impact of monetary policy on consumption due to changes in interest rates is larger and more sensitive than investment, according to the impulse response test. The main channel of the effect of policy shocks obtained from consumption is transmitted to output. Therefore, the monetary policy issued by Bank Indonesia will have a greater impact on household spending than corporate spending. This means that channel consumption is the main mechanism of transmission.